The enhancement of residual electric field in water electrolysis by green laser irradiation - Ab. Razak, Siti Noraiza (2015)
Hydrogen energy produced by water electrolysis is considered free from green house effect. However such production still lacks in efficiency. Therefore we proposed an efficient system to increase the hydrogen production by introducing a green laser in the water electrolysis system. In this work a diode-pumped solid state laser operating in second harmonic generation (green laser) was employed as a source of external electric field. The green laser was illuminating directly into a water electrolysis chamber. The power of the laser was varied in the range of 0 to 200 mW. Conventional electrolysis and electrolysis using white light from halogen lamp were also conducted for comparison purposes. The effect of green laser was further characterized based on beam direction, angle and displacement. The direction of the beam was set either in direction or in opposite direction to the electric field. The beam angle was varied in the range from 0° to 180? and the displacement is varied within 0 to 6 mm from the end of electrode. The result obtained showed that the hydrogen production corresponding to green laser electrolysis is dependent on the power of the laser. Higher laser power will contribute to higher hydrogen production. The rate of hydrogen production is 1.17 ml min-1 with green laser, 0.80 ml min-1 in response to white light and 0.67 ml min-1 for conventional electrolysis. The rate of hydrogen production is 1.33 ml min-1 when light is illuminated from cathode to anode (in direction with residual electric field) and 0.267 ml min-1 in the opposite direction. The hydrogen production is found inversely proportional with regard to beam angle. When the angle of irradiation is increased, the hydrogen production rate decreases. Besides, the highest hydrogen production can be achieved when the beam displacement is at zero distance from the electrodes. This means that the beam essentially connects the end of electrodes that allows fast flow of current of the closed electric circuit in the electrolysis system. In conclusion, green laser has positive impact on the hydrogen production because it contributes extra electric field to enhance the weak residual electric field caused by the polarizability property of water.